Memaksimalkan Peran Dana Wakaf untuk Pengembangan Industri Halal: Sebuah Kerangka Optimalisasi - INDAH MAESAROH; Nuryitmawan, Tegar Rismanuar (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2023)
This research aims to propose a business framework that aims to maximise the role of waqf funds towards the halal ecosystem in Indonesia. We aimed to evaluate the flexibility of waqf funds as a low-cost source of funds that can trigger the growth of MSE businesses. A qualitative approach is used, especially a library research approach from various data sources of previous studies. The results show that cash waqf management institutions can empower by providing assistance in the form of investment capital or capital for business sustainability so that the management of waqf funds becomes more productive. This study found two approaches in the business process of channeling waqf funds to Islamic microfinance institutions, namely top down and bottom up, which have the aim of improving business performance and business scale. the financing requirements carried out, especially for MSEs that have halal certification, are expected to advance Indonesia's halal industry and increase the value of exports with a wider range. Keywords: Waqf Fund, Halal Industry, Islamic microfinance institutions